Model and control of fuel supply systems of hydrogen/oxygen fuel cell. Issue 13 (4th December 2017) - Cheng, Zhiping; Ren, Peng; Xu, Ya Li; Zhang, Han Nian
Abstract : Fuel supply systems have a great impact on output characteristics and lifetime of the hydrogen/oxygen fuel cell. On the basis of the fuel supply systems of the fuel cell, this study has studied the models of hydrogen supply system and oxygen supply system. Moreover, the fuzzy self‐adaptive proportional–integral–derivative (PID) controllers for hydrogen supply system are designed according to the characteristics of hydrogen and oxygen supply systems. The simulation results show that fuzzy self‐adaptive PID control method can achieve better performance for supply system.